A kind of environmentally friendly energy storage brick based on foundry waste sand and preparation method thereof
By using cast waste sand, magnesium sand and other materials, combined with high temperature activation and sintering processes, environmentally friendly energy storage bricks with high strength and excellent heat storage performance are prepared, which solves the problems of inconvenient treatment of cast waste sand and high cost of energy storage bricks, and achieves efficient reuse of resources and environmental protection.
Patent Information
- Application Number
- CN202411922335.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
AI Technical Summary
The existing casting industry faces the problems of inconvenient treatment of waste sand, waste of resources and high cost of energy storage bricks, and magnesium sand bricks are prone to deform within a wide temperature range and have poor stability.
Cast waste sand, magnesium sand, fly ash, paraffin wax, potassium nitrate, sodium chloride, water glass and iron powder are used as raw materials, and environmentally friendly energy storage bricks with high strength and excellent heat storage properties are prepared through high-temperature activation, ball milling, pressurization molding and sintering processes.
It realizes efficient reuse of cast waste sand, reduces the cost of energy storage bricks, improves the strength and heat storage performance of energy storage bricks, meets a wider energy storage demand, and reduces environmental pollution.
Smart Images

Figure CN119751019A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage materials, and more particularly to an environmentally friendly energy storage brick based on foundry waste sand and a preparation method thereof. Background Art
[0002] As a pillar industry of my country's national economy, casting has long been ranked first in the world in terms of casting output. There are many casting methods. Among them, silicate binder sand (commonly known as water glass sand) is an environmentally friendly casting sand. Due to its low pollution and low gas emission characteristics, it is in line with the national industrial development direction and significantly reduces the harm to the health of foundry workers. In recent years, it has been widely used instead of organic resin sand, solving the long-term high pollution and harmful gas problems of sand casting. However, in addition to this, due to the high sand-iron ratio problem in sand casting, the weight of the waste sand produced is usually 1 to 1.5 times the output of castings. There are two main ways to treat the waste sand. One is to mix it into new sand through multiple reprocessing methods before further use. However, the treatment method is generally cumbersome, with large equipment investment and high operating costs. However, the performance of the recycled waste sand is still somewhat different from that of the new sand. Now, more practices are to directly landfill or discard the waste sand of water glass, which not only causes serious pollution to the ecological environment, but also causes a great waste of resources.
[0003] How to achieve efficient recycling of waste foundry sand is an urgent problem that needs to be solved in the foundry industry.
[0004] At the same time, the existing energy storage bricks are mainly magnesia bricks. The energy storage principle is to absorb and release heat when the material undergoes phase change. The main component of magnesia is magnesium oxide, which is an alkali metal oxide. It has stable performance and strong insulation under high temperature and high pressure. Even in an environment above 800°C, it still has relatively high fire-resistant insulation performance. In addition, magnesium oxide has a high specific heat capacity, and the energy storage working temperature can be as high as 1600°C. Due to its advantages such as high efficiency, high density, long storage time, and wide application range, it is widely used in energy storage stations, smart grids, microgrids and other fields. However, the current reason restricting the further development of magnesia bricks is that the price of magnesia is relatively high compared to other types of sand. At the same time, the linear expansion coefficient of magnesium oxide is also high. When used in a wide temperature range, it is easy to shrink and expand, causing the energy storage bricks to deform and reduce stability.
[0005] The main component of casting waste sand is silicon dioxide, which has high refractoriness and low linear expansion coefficient. Using it to replace part of magnesia sand as the skeleton material of energy storage bricks can achieve the recycling of casting waste, reduce the price of energy storage bricks, and reduce the linear expansion coefficient of energy storage bricks, thereby reducing the cost and increasing the efficiency of the preparation of magnesia sand energy storage bricks. Summary of the invention
[0006] In view of this, the present invention provides a foundry waste sand-based environmentally friendly energy storage brick and a preparation method thereof, using foundry waste sand, magnesia sand, fly ash, paraffin, potassium nitrate, sodium chloride, water glass, and iron powder as raw materials. The main materials of the present invention are all industrial wastes, foundry waste sand is foundry waste, and fly ash is power plant waste, all of which are produced under high temperature environment and have good thermal stability. As the skeleton material of the energy storage brick, it can provide higher strength.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A foundry waste sand-based environmentally friendly energy storage brick comprising: a base material, a phase change agent, a thermal conductive material and a binder;
[0009] Wherein, the matrix material includes fly ash, foundry waste sand and magnesia sand;
[0010] The phase change agent includes sodium chloride, potassium nitrate solution, and paraffin;
[0011] The thermally conductive material includes iron powder;
[0012] The binder includes water glass.
[0013] Preferably, the mass ratio of the fly ash, foundry waste sand and magnesia is 1:10:10.
[0014] Preferably, the percentage of each component in the phase change agent to the total mass of the base material is: 2% sodium chloride, 3% potassium nitrate solution and 3% paraffin.
[0015] Preferably, the percentage of the thermal conductive material to the total mass of the base material is: iron powder 2%.
[0016] Preferably, the percentage of the binder to the total mass of the base material is: 5% water glass.
[0017] Among the components of the present invention, (1) magnesia can realize energy storage in a wide temperature range.
[0018] (2) The phase change temperature of paraffin is about 50°C, the phase change temperature of potassium nitrate is about 337°C, and the phase change temperature of sodium chloride is 810°C. Different from the existing magnesia energy storage bricks and simple phase change agent magnesia bricks, the composite phase change agent can enhance the low-temperature, medium-temperature and high-temperature phase change latent heat, and improve the heat storage capacity and operating temperature range of the energy storage bricks.
[0019] (3) The main function of water glass (sodium silicate) is to improve the strength of energy storage bricks. Its volatilization temperature is above 900°C, which is outside the operating temperature range. Its main component is sodium silicate, and no polluting gas is generated during preparation and use. Compared with polyvinyl alcohol commonly used in existing energy storage bricks, the addition of water glass is a green binder that is non-toxic and harmless. On the other hand, the strength of water glass will be significantly enhanced at high temperatures. This problem of too high collapse strength during casting is just utilized in the present invention.
[0020] (4) The addition of iron powder can improve the thermal conductivity of energy storage bricks, which is conducive to timely heat absorption and heat release.
[0021] (5) The present invention uses foundry waste sand, which solves the problem of recycling and reusing foundry waste sand to prepare environmentally friendly energy storage materials. On the other hand, it makes full use of the binder in the waste sand. Compared with ordinary silica sand, the residual binder can improve the strength of the energy storage bricks.
[0022] Another object of the present invention is to provide a method for preparing the foundry waste sand-based environmentally friendly energy storage brick as described above, comprising the following steps:
[0023] (1) Processing of foundry waste sand: crushing and ball milling of foundry waste sand;
[0024] (2) Mixing of matrix materials: The fly ash is activated at high temperature, and then mixed with foundry waste sand and magnesia sand in a ratio of 1:10:10 until fully mixed. These additives can also be mixed in advance according to the proportion. This addition amount is the maximum addition amount of various additives that does not affect the strength of the energy storage brick;
[0025] (3) adding a phase change agent and mixing; sequentially adding 2% sodium chloride powder, 3% potassium nitrate solution, and 3% paraffin powder to the matrix material mixture and mixing until fully mixed;
[0026] (4) Add thermal conductive material and mix; add 2% iron powder to the matrix material mixture in sequence and mix until fully mixed;
[0027] (5) Adding binder to the mixture: Add 5% of the mass of water glass to the matrix material mixture and mix until it is uniform. This amount is the most obvious amount to improve the strength of the energy storage brick. After that, even if the amount of water glass is increased, the strength of the energy storage brick is not significantly improved;
[0028] (6) Pressurized molding: Apply pressure inside the energy storage brick mold to make the energy storage brick compact, increase the density of the energy storage brick, and shape the energy storage brick by extrusion force, but the strength is low at this time;
[0029] (7) Heating and curing: Place the energy storage brick sample in a blast drying oven to dry it so that the water glass is completely cured. At this time, the strength of the energy storage brick can reach a relatively high level;
[0030] (8) Sintering into bricks: Place the bricks in a muffle furnace for sintering, and then cool them to room temperature with the furnace to avoid rapid cooling. The expansion coefficient of iron powder and other components is too large, which may cause the energy storage bricks to crack and affect the strength of the energy storage bricks. After the sintering operation, the strength of the energy storage bricks reaches the standard.
[0031] Preferably, the temperature of the high temperature activation in step (2) is 800° C.; the particle size of the foundry waste sand is 40-100 mesh; and the particle size of the magnesia sand is 1-3 mm.
[0032] Preferably, the pressure in step (6) is 50 MPa.
[0033] Preferably, the drying in step (7) is performed at 100° C. for 30 min.
[0034] Preferably, the sintering in step (8) is performed at 800° C. for 3 hours.
[0035] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) Industrial waste is turned into treasure, and the cost of brick making is significantly reduced. Industrial waste is recycled to produce environmentally friendly products. Foundries and power plants are widely distributed in my country and are numerous. The waste generated by them is mainly waste sand and fly ash. The recycling process is cumbersome and even difficult to recycle. Even if it is recycled, its performance will be significantly reduced. The present invention can realize the transformation of process waste into treasure and make products that can play a role for a long time. At the same time, because the present invention uses low-cost industrial waste to replace more than half of the magnesia, the cost of energy storage bricks is reduced by more than 30%;
[0037] (2) The strength of energy storage bricks produced exceeds that of magnesia sand bricks. On the one hand, the residual binder in the waste sand from castings can be solidified again under the action of high temperature during the preparation of energy storage bricks, which plays a role in strengthening the performance of energy storage bricks. On the other hand, the present invention additionally adds thermosetting water glass (sodium silicate solution) as a binder. Water glass is a commonly used binder for casting, which is green, non-toxic and pollution-free. However, it has a fatal drawback when used, that is, after the molten metal is poured at more than one thousand degrees, the strength does not decrease but increases, resulting in poor collapsibility of the sand mold during production, and the sand mold is difficult to break. However, when it is used as an energy storage brick binder, when it is roasted at 800°C and actually used at higher temperatures, it is beneficial to enhance the strength performance of the energy storage brick sample to exceed that of magnesia sand bricks, and meet more diverse energy storage requirements.
[0038] (3) The energy storage and heat storage performance of the bricks made by the present invention is better than that of magnesia sand bricks. Based on the heat storage performance of magnesia sand itself, three phase change agents with excellent heat storage performance at low, medium and high temperatures are innovatively added to magnesia sand bricks. Each phase change agent relays heat storage in different temperature ranges. On the one hand, it greatly increases the use range of energy storage bricks, and energy storage can be achieved from 50-900°C; on the other hand, compared with the traditional energy storage that only relies on magnesia sand or a single phase change agent, the three phase change agents greatly increase the energy storage capacity of the energy storage conversion, and the cumulative heat storage density is more than 10 times that of common magnesia sand bricks;
[0039] (4) The energy storage bricks prepared by the present invention can achieve the performance index of magnesia energy storage bricks, with a volume density of ≥3.0g / cm 3 , compressive strength ≥40MPa, flexural strength ≥12MPa, linear expansion coefficient ≤3%, thermal conductivity ≥0.3w / m·k, specific heat capacity ≥0.8kJ / kg.℃, material phase change temperature controlled at 50-900℃, phase change latent heat 70-90J / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0041] Figure 1 The present invention is a process flow chart for preparing the same;
[0042] Figure 2 This is a photo of the final sample-to-finished product obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] This embodiment provides a method for preparing a foundry waste sand-based environmentally friendly energy storage brick, comprising the following steps:
[0046] (1) Processing of waste sand: crushing and ball milling of foundry waste sand;
[0047] (2) Matrix material mixing: fly ash is activated at 800°C, and mixed with waste sand (mostly 40-100 mesh) and magnesia (1-3 mm) in a ratio of 1:10:10 until fully mixed;
[0048] (3) Add phase change agent and mix; add 2% sodium chloride powder, 3% potassium nitrate solution and 3% paraffin powder to the sand mixture in sequence and mix until fully mixed. These additives can also be mixed in advance according to the proportion. This addition amount is the maximum addition amount of various additives that does not affect the strength of the energy storage brick;
[0049] (4) Add thermal conductive material and mix: Add 2% iron powder to the matrix material mixture and mix until it is uniform.
[0050] (5) Adding binder to the mixture: Add 5% of the mass of water glass to the sand mixture and mix until it is uniform. This amount is the most obvious amount to improve the strength of the energy storage brick. After that, even if the amount of water glass is increased, the strength of the energy storage brick is not significantly improved;
[0051] (6) Pressurized molding: Apply 50Mpa pressure in a specific energy storage brick mold to make the energy storage brick compact, increase the density of the energy storage brick, and shape the energy storage brick by extrusion force, but the strength is low at this time;
[0052] (7) Heating and curing: Place the energy storage brick sample in a 100°C forced air drying oven for 30 minutes to completely cure the water glass. At this time, the strength of the energy storage brick has reached a relatively high level.
[0053] (8) Sintering into bricks: Keep in a muffle furnace at 800℃ for 3 hours, and then cool to room temperature with the furnace to avoid rapid cooling. The expansion coefficient of iron powder and other components is too large, which may cause the energy storage bricks to crack and affect the strength of the energy storage bricks. After the sintering operation, the strength of the energy storage bricks reaches the standard.
[0054] Comparative Example 1
[0055] A phase change heat storage brick and a preparation method thereof. The specific steps are as follows:
[0056] (1) MgO with a particle size of 40 μm and MS-96 with a particle size of 0.5 mm were fully mixed in a mass ratio of 9:1 to prepare a skeleton material for later use;
[0057] (2) Evenly mix LizCO3, Na2CO3 and KCO3 in a mass ratio of 2.2:48.6:49.2 to prepare a phase change material for later use;
[0058] (3) Weigh out polyvinyl alcohol aqueous solution and borax in a mass ratio of 4:6 respectively for later use. Here, the mass ratio of the skeleton material, the phase change material and the binder is 32:60:8;
[0059] (4) The skeleton material, phase change material and sodium silicate are added to the mixer in sequence, and the mixing time is set to 40 minutes. Then it is transferred to the kneading machine, and 3% polyvinyl alcohol is added at the same time, and kneaded for 30 minutes. After that, the kneaded material is pre-pressed into a brick shape at a pressure of 20MPa, and then sintered in an environment of 550°C for 3 hours;
[0060] (5) crushing the sintered bricks and ball milling them for 3 hours, followed by kneading and pressing again, wherein the kneading time is 30 minutes and the pressure is 25 MPa;
[0061] (6) The formed bricks are subjected to secondary sintering, the sintering temperature is set to 690°C, the sintering time is 2 hours, and the heating rate is 5°C / min, and finally a phase change heat storage brick is obtained.
[0062] Comparative Example 2
[0063] A phase change heat storage brick and a preparation method thereof. The specific steps are as follows:
[0064] (1) Processing the waste sand: crushing and ball milling the foundry waste sand; subjecting the fly ash to high temperature activation at 800°C, and mixing it with the waste sand (mostly 40-100 mesh) and magnesia (1-3 mm) in a ratio of 1:10:10 until fully mixed;
[0065] (2) Add 2% sodium chloride powder and 2% iron powder to the sand mixture in sequence and mix until fully mixed; add 5% water glass by weight of the sand mixture and mix until uniform;
[0066] (3) Apply 50Mpa pressure in a specific energy storage brick mold to make the energy storage brick compact, increase the density of the energy storage brick, and shape the energy storage brick by extrusion force;
[0067] (4) Place the energy storage brick sample in a 100°C forced air drying oven for 30 minutes;
[0068] (5) Keep in a muffle furnace at 800 °C for 3 h and then cool to room temperature.
[0069] Comparative Example 3
[0070] A phase change heat storage brick and a preparation method thereof. The specific steps are as follows:
[0071] (1) Processing of waste sand: crushing and ball milling of foundry waste sand;
[0072] (2) The fly ash is activated at 800°C and mixed with waste sand (mostly 40-100 mesh) and magnesia (1-3 mm) in a ratio of 1:10:10 until fully mixed;
[0073] (3) Add 2% sodium chloride powder, 3% potassium nitrate solution, and 3% paraffin powder to the sand mixture in sequence until fully mixed;
[0074] (4) Add 5% of water glass to the sand mixture and mix until it is uniform;
[0075] (5) Apply 50Mpa pressure in a specific energy storage brick mold to make the energy storage brick compact, increase the density of the energy storage brick, and shape the energy storage brick by extrusion force;
[0076] (6) Place the energy storage brick sample in a 100°C forced air drying oven for 30 minutes;
[0077] (7) Keep it in a muffle furnace at 800 °C for 3 h and then cool it to room temperature.
[0078] Comparative Example 4
[0079] A phase change heat storage brick and a preparation method thereof. The specific steps are as follows:
[0080] (1) Processing of waste sand: crushing and ball milling of foundry waste sand;
[0081] (2) The fly ash is activated at 800°C and mixed with waste sand (mostly 40-100 mesh) and magnesia (1-3 mm) in a ratio of 1:10:10 until fully mixed;
[0082] (3) Add 2% sodium chloride powder, 3% potassium nitrate solution, 3% paraffin powder, and 2% iron powder to the sand mixture in sequence until fully mixed;
[0083] (4) adding 5% of polyvinyl alcohol by weight of the sand mixture and mixing until uniform;
[0084] (5) Apply 50Mpa pressure in a specific energy storage brick mold to make the energy storage brick compact, increase the density of the energy storage brick, and shape the energy storage brick by extrusion force;
[0085] (6) Place the energy storage brick sample in a 100°C forced air drying oven for 30 minutes;
[0086] (7) Keep in a muffle furnace at 800 °C for 3 h and then cool to room temperature.
[0087] Comparative Example 5
[0088] A phase change heat storage brick and a preparation method thereof. The specific steps are as follows:
[0089] (1) Processing of waste sand: crushing and ball milling of foundry waste sand;
[0090] (2) The fly ash is activated at 800°C and mixed with waste sand (mostly 40-100 mesh) and magnesia (1-3 mm) in a ratio of 1:10:10 until fully mixed;
[0091] (3) Add 3% sodium chloride powder, 4% potassium nitrate solution, 4% paraffin powder, and 2% iron powder to the sand mixture in sequence until fully mixed;
[0092] (4) Add 5% of water glass to the sand mixture and mix until it is uniform;
[0093] (5) Apply 50Mpa pressure in a specific energy storage brick mold to make the energy storage brick compact, increase the density of the energy storage brick, and shape the energy storage brick by extrusion force;
[0094] (6) Place the energy storage brick sample in a 100°C forced air drying oven for 30 minutes;
[0095] (7) Keep in a muffle furnace at 800 °C for 3 h and then cool to room temperature.
[0096] Comparative Example 6
[0097] A phase change heat storage brick and a preparation method thereof. The specific steps are as follows:
[0098] (1) Processing of waste sand: crushing and ball milling of foundry waste sand;
[0099] (2) The fly ash is activated at 800°C and mixed with waste sand (mostly 40-100 mesh) and magnesia (1-3 mm) in a ratio of 1:10:10 until fully mixed;
[0100] (3) Add 1% sodium chloride powder, 2% potassium nitrate solution, 2% paraffin powder, and 2% iron powder to the sand mixture in sequence until fully mixed;
[0101] (4) Add 5% of water glass to the sand mixture and mix until it is uniform;
[0102] (5) Apply 50Mpa pressure in a specific energy storage brick mold to make the energy storage brick compact, increase the density of the energy storage brick, and shape the energy storage brick by extrusion force;
[0103] (6) Place the energy storage brick sample in a 100°C forced air drying oven for 30 minutes;
[0104] (7) Keep in a muffle furnace at 800 °C for 3 h and then cool to room temperature.
[0105] Energy storage performance test results of examples and comparative examples 1-6
[0106]
[0107] From the above results, compared with comparative example 1, the phase change energy storage converter proposed in the embodiment has better heat storage performance and strength performance than the magnesia sand phase change energy storage converter due to the reasonable addition of multiple phase change agents and other additives, and the sample state after 100 cycles is almost the same as the magnesia sand energy storage converter. At the same time, the use of foundry waste sand instead of magnesium oxide and part of magnesia sand can greatly reduce the price of the energy storage converter.
[0108] Compared with Example 1 and Comparative Example 2, although the addition of multiple phase change agents will slightly reduce the strength, the heat storage density is greatly improved.
[0109] Compared with Example 1 and Comparative Example 3, after the iron oxide powder is added, the thermal conductivity of the sample is greatly improved due to the good thermal conductivity of the iron oxide powder itself.
[0110] Compared with Example 1 and Comparative Example 4, compared with polyvinyl alcohol, the addition of water glass can greatly improve the strength performance of the energy storage converter by room temperature curing and high temperature secondary curing.
[0111] Compared with Example 1 and Comparative Example 5, the addition amounts of the three phase change agents, namely paraffin, potassium nitrate and sodium chloride, are higher than those of the present invention. Excessive phase change materials affect the strength of the energy storage converter on the one hand, and on the other hand, cause thermal deformation of the energy storage converter and reduce thermal stability.
[0112] Compared with Example 1 and Comparative Example 6, the addition amount of the three phase change agents, paraffin, potassium nitrate and sodium chloride, is lower than that of the present invention, and the strength of the sample will increase to a certain extent, but the strength of the embodiment is still at a high level, and the heat storage performance will decrease accordingly. Combined with Comparative Example 5 and Comparative Example 6, the addition amount of the three phase change agents proposed by the present invention is the best point to ensure the energy storage strength and heat storage performance.
[0113] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0114] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A foundry waste sand-based environmentally friendly energy storage brick, characterized in that: include: Matrix materials, phase change agents, adhesives and thermal conductive materials; Wherein, the matrix material includes foundry waste sand, magnesia sand and fly ash; The phase change agent includes sodium chloride, potassium nitrate solution, and paraffin; The binder includes water glass; The thermally conductive material includes iron powder.
2. The foundry waste sand-based environmentally friendly energy storage brick according to claim 1, characterized in that: The mass ratio of the fly ash, foundry waste sand and magnesia sand is 1:10:
10.
3. The foundry waste sand-based environmentally friendly energy storage brick according to claim 2, characterized in that: The percentage of each component in the phase change agent to the total mass of the base material is: 2% sodium chloride, 3% potassium nitrate solution, and 3% paraffin.
4. The foundry waste sand-based environmentally friendly energy storage brick according to claim 3, characterized in that: The percentage of the binder to the total mass of the base material is: water glass 5%.
5. The foundry waste sand-based environmentally friendly energy storage brick according to claim 4, characterized in that: The percentage of the heat conductive material to the total mass of the base material is: 2% iron powder.
6. A method for preparing the foundry waste sand-based environmentally friendly energy storage bricks as claimed in claim 5, characterized in that: The following steps are involved: (1) Processing of foundry waste sand: crushing and ball milling of foundry waste sand; (2) Mixing of matrix materials: The fly ash is activated at high temperature, and then mixed with foundry waste sand and magnesia sand in a ratio of 1:10:10 until fully mixed; (3) adding a phase change agent and mixing; sequentially adding 2% sodium chloride powder, 3% potassium nitrate solution, and 3% paraffin powder to the matrix material mixture and mixing until fully mixed; (4) Adding thermal conductive material and mixing: adding iron powder accounting for 2% of the mass of the matrix material mixture and mixing until uniform; (5) Adding binder to the mixture: adding 5% of water glass by weight of the matrix material mixture and mixing until uniform; (6) Pressurization molding: Apply pressure in the energy storage brick mold to make the energy storage brick compact, increase the density of the energy storage brick, and shape the energy storage brick by extrusion force; (7) Heating and curing: Place the energy storage brick sample in a blast drying oven to dry it so that the water glass is completely cured; (8) Sintering into bricks: Sintering in a muffle furnace, and then cooling to room temperature with the furnace to obtain the energy storage bricks.
7. The method for preparing a foundry waste sand-based environmentally friendly energy storage brick according to claim 6, characterized in that: The temperature of high temperature activation in step (2) is 800° C.; the particle size of the foundry waste sand is 40-100 mesh; and the particle size of the magnesia sand is 1-3 mm.
8. The method for preparing a foundry waste sand-based environmentally friendly energy storage brick according to claim 6, characterized in that: The pressure in step (6) is 50 MPa.
9. The method for preparing a foundry waste sand-based environmentally friendly energy storage brick according to claim 6, characterized in that: The drying in step (7) is performed at 100° C. for 30 min.
10. The method for preparing a foundry waste sand-based environmentally friendly energy storage brick according to claim 6, characterized in that: The sintering in step (8) is performed at 800° C. for 3 hours.